2019
DOI: 10.37236/8833
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Decompositions and the Smallest-eigenvalue Separation

Abstract: A new method is introduced for bounding the separation between the value of −k and the smallest eigenvalue of a non-bipartite k-regular graph. The method is based on fractional decompositions of graphs. As a consequence we obtain a very short proof of a generalization and strengthening of a recent result of Qiao, Jing, and Koolen [5] about the smallest eigenvalue of non-bipartite distance-regular graphs. arXiv:1907.08447v1 [math.CO]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…In Section 2, we use weighted graph decompositions of the edge set of a graph to bound the spectrum of a graph from below. Our results are similar and have been obtained independently from the recent work of Knox and Mohar [27].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Section 2, we use weighted graph decompositions of the edge set of a graph to bound the spectrum of a graph from below. Our results are similar and have been obtained independently from the recent work of Knox and Mohar [27].…”
Section: Introductionsupporting
confidence: 91%
“…If S = 2 uv∈M x u x v , then S ≤ 4(1−S) (λ−1) 2 which implies that S ≤ 4 4+(λ−1) 2 . Plugging this into (25), we get that λ ≥ −2 − 4 4 + (λ − 1) 2 (27) which implies that λ 3 − λ + 14 ≥ 0. Hence, λ ≥ θ ≈ −2.272.…”
Section: Proposition 44mentioning
confidence: 98%
“…Using fractional decomposition of graphs, Knox-Mohar have shown that the smallest eigenvalue of the normalized adjacency operator of a undirected, regular, nonbipartite, distance-regular graph with odd girth g is greater than or equal to 1 − cos π g [19,Corollary 5], generalizing and strengthening a result of Qiao-Jing-Koolen [26, Theorem 1].…”
Section: Arindam Biswas and Jyoti Prakash Sahamentioning
confidence: 83%
“…Aharoni, Alon, and Berger [2] obtained a lower bound for the smallest eigenvalue of a regular graph where each vertex is contained in many triangles (see also [8]). Knox and Mohar [21] obtained a lower bound for the smallest eigenvalue using graph decompositions and their work leads to a simpler proof of a result of Qiao, Jing, and Koolen [33] on the smallest eigenvalue of a distance-regular graph.…”
Section: Introductionmentioning
confidence: 99%